2008
DOI: 10.3171/foc.2008.25.11.e6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure protection and attenuation of lipid peroxidation after blockade of presynaptic release of glutamate by lamotrigine in experimental spinal cord injury

Abstract: Object Lamotrigine is an antiepileptic drug that inhibits presynaptic voltage-gated sodium channels and reduces the presynaptic release of glutamate in pathological states. Neuroprotective effects of this drug have already been demonstrated in cerebral ischemia models. The aim of the present study was to determine the effects of presynaptic glutamate release inhibition on experimental spinal cord injury (SCI). Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In humans, SCI is most commonly caused by a combination of acute impact and persistent compression and shows two consecutive stages (5). First, the vertebral fracture fragments Several studies have investigated pharmacologic agents that were presumed to have neuroprotective effects after SCI, but only methylprednisolone has shown beneficial effects in large clinical studies (13-15, 30,31,33). Although it has beneficial effects on parenchymal damage, there is no significant improvement of functional recovery (25).…”
Section: █ Introductionmentioning
confidence: 99%
“…In humans, SCI is most commonly caused by a combination of acute impact and persistent compression and shows two consecutive stages (5). First, the vertebral fracture fragments Several studies have investigated pharmacologic agents that were presumed to have neuroprotective effects after SCI, but only methylprednisolone has shown beneficial effects in large clinical studies (13-15, 30,31,33). Although it has beneficial effects on parenchymal damage, there is no significant improvement of functional recovery (25).…”
Section: █ Introductionmentioning
confidence: 99%
“…Although the anti-oxidant effect of LTG in an experimental model of spinal cord injury (15), however, hepatic reactions to LTG ranged from transient elevation of hepatic enzymes without clinical signs or symptoms of hepatic dysfunctions to fatal hepatotoxicity . In the light of potential toxicity, clinicians prescribing LTG as a single therapy or polytherapy must have attention to the possibility of occurance of an autoimmune LTG-induced hepatitis up to reaching many serious hepatic reactions particularly in case of polytherapy with enzyme inducing drugs as carbamazepine, keeping in mind that many antiepileptic drugs, possess an apparent anti-oxidant effect on different body organs e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that possible GABAergic mechanism has a role in the neuroprotective effect of gabapentin and lamotrigine against 3-nitropropionic acid induced neurotoxicity (Kumar et al, 2012). Neuroprotective effects of LMG have been demonstrated in cerebral ischemia models (Tufan et al, 2008). Lamotrigine acts as a mood stabilizer by inhibiting excessive glutamate release but NMDA receptor-mediated glutamate transmission is important in the formation of long term potentiation and learning and memory.…”
Section: Discussionmentioning
confidence: 98%